مجالات الضيافة والكرم من خلال تفسير الشيخ الشعراوي: دراسة موضوعية - Ahmad Salahuddin M. Azizan (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BA020 1033-1053